Edge-selectively antimony-doped graphene nanoplatelets as an outstanding counter electrode with an unusual electrochemical stability for dye-sensitized solar cells employing cobalt electrolytes. Issue 23 (21st April 2016) - Kim, Hong Mo; Jeon, In-Yup; Choi, In Taek; Kang, Sung Ho; Shin, Sun-Hee; Jeong, Hu Young; Ju, Myung Jong; Baek, Jong-Beom; Kim, Hwan Kyu
Abstract : Edge-selectively antimony-doped graphene nanoplatelet electrocatalysts exhibited an extremely low charge transfer resistance with "zero-loss stability" for a cobalt redox couple. Abstract : A dye-sensitized solar cell (DSSC), one of the present photovoltaic technologies, has always been associated with some problems that make them unsatisfactory for practical use. Among them, developing low-cost, durable, and highly active electrocatalysts such as platinum (Pt) alternatives is one of the urgent issues for practical and/or large-scale commercial applications. In this study, as one of the feasible Pt alternatives, edge-selectively antimony-doped graphene nanoplatelets (SbGnPs) were prepared by a simple eco-friendly mechanochemical reaction between pristine graphite and Sb powder for the use of a counter electrode (CE) in dye-sensitized solar cells, for the first time. The selective doping of metalloid Sb at the edges of graphene nanoplatelets (GnPs) and their structure were confirmed by various analytical techniques including atomic-resolution transmission electron microscopy (AR-TEM). The resultant SbGnPs exhibited a much lower charge-transfer resistance ( R ct ) compared to that of Pt as electrocatalysts toward a Co(bpy)3 2+/3+ (bpy = 2, 2′-bipyridine) redox couple, displaying 'zero loss stability' of electrocatalytic activity for the Co(bpy)3 3+ reduction reaction even after 1000 potential cycles. DSSCs employing Co(bpy)3 2+/3+ were systematically evaluated in a comparison with the N-doped graphene nanoplatelet (NGnP) CE as a reference. The SbGnP-CE-based DSSC employing anSGT-021 sensitizer based on a D–π–A structured zinc(ii )-porphyrin showed better power conversion efficiency (12.08%) than the Pt (11.26%) or the NGnPs (11.53%). The outstanding electrocatalytic activity of the SbGnPs with an unusual electrochemical stability suggests that they could be a possible candidate as the best alternative to a Pt-CE for DSSCs in conjunction with cobalt electrolytes.